2006
DOI: 10.1079/bjn20061562
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of β-carotene (βC) from purple carrots is the same as typical orange carrots while high-βC carrots increase βC stores in Mongolian gerbils(Meriones unguiculatus)

Abstract: Vitamin A (VA) deficiency is a worldwide public health problem. Biofortifying existing sources of b-carotene (bC) and increasing dietary bC could help combat the issue. Two studies were performed to investigate the relative bC bioavailability of a bC supplement to purple, high-bC orange, and typical orange carrots using Mongolian gerbils (Meriones unguiculatus). In study 1, which used a traditional bioavailability design, gerbils (n 32) received a diet containing orange, purple, or white carrot powder, or whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
3
19
2
Order By: Relevance
“…34 In humans and gerbils, extra dietary carotenoid that is not converted to retinol is absorbed and stored, but not currently considered when determining bioavailability. The βC absorbed from biofortified carrot and stored in the liver was 2650% higher in the prior study at 3.3% 21 than the current study at 0.5% of the feed. Carrot intake, in contrast to VA supplements, impacts antioxidant capacity of tissues and may support optimal health.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…34 In humans and gerbils, extra dietary carotenoid that is not converted to retinol is absorbed and stored, but not currently considered when determining bioavailability. The βC absorbed from biofortified carrot and stored in the liver was 2650% higher in the prior study at 3.3% 21 than the current study at 0.5% of the feed. Carrot intake, in contrast to VA supplements, impacts antioxidant capacity of tissues and may support optimal health.…”
Section: Discussioncontrasting
confidence: 66%
“…In prior studies, high-βC carrots provided an abundant amount of retinol to gerbils. 21 In study 2, the hypothesis was that small amounts of high-βC carrots will be an effective complementary food to maintain liver retinol reserves in gerbils despite potential effects of the combined food matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, serum retinol concentrations improved in young children after the introduction of OFSP into Mozambique (14). The Mongolian gerbil model (15) has been used to assess bioefficacy of a-carotene (16), bC (17)(18)(19)(20), and b-cryptoxanthin (21) from supplements, carrots (17)(18)(19), maize (22), cassava (23), and green vegetables (23). The gerbil model provides estimates of dietary provitamin A bioefficacy and is ideal for studying whole-body metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Carrots have been well studied for provitamin A conversion, with most studies focusing solely on determining the total carotene contribution to vitamin A (17)(18)(19). Although other groups have demonstrated that a-retinol is esterified and cleared from the enterocyte into plasma in animal models (9,11,28), this is the first postprandial study, to our knowledge, to follow aRP in human plasma.…”
Section: Discussionmentioning
confidence: 95%
“…The structural similarity of a-retinyl esters to retinyl esters causes co-elution with most HPLC methods (11,14,15). Although studies have assessed the absorption and conversion of a-and b-carotene to vitamin A in animals (9,10,17,18) and humans (19,20), vitamin A equivalence has likely been overestimated because of the contribution of a-retinyl esters to the newly converted retinyl esters. We developed a method to separate a-retinyl esters from retinyl esters for a more accurate quantitation of vitamin A derived from a meal containing a-carotene (21).…”
Section: Introductionmentioning
confidence: 99%